2014
DOI: 10.1182/blood-2013-08-523563
|View full text |Cite
|
Sign up to set email alerts
|

Tiam1/Rac1 signals contribute to the proliferation and chemoresistance, but not motility, of chronic lymphocytic leukemia cells

Abstract: Key Points Motility of resting CLL cells requires chemokine-mediated RhoA activation but is independent of Tiam1/Rac signals. Tiam1/Rac signals are indispensible for CLL cell proliferation and chemoresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 63 publications
(56 reference statements)
4
53
0
Order By: Relevance
“…These results suggest that 6-TG inhibits T-cell development. Studies show that the Rac1 activity is involved in T-cell proliferation and viability (45)(46)(47). Within this study, we provide evidence that the 6-TG-mediated Rac1 inactivation is because of the formation of the inactive 6-TGDP-Rac1 adduct in CD4 ϩ cells.…”
Section: Inhibitory Effects Of 6-tg and A Redox Agent On Development mentioning
confidence: 57%
“…These results suggest that 6-TG inhibits T-cell development. Studies show that the Rac1 activity is involved in T-cell proliferation and viability (45)(46)(47). Within this study, we provide evidence that the 6-TG-mediated Rac1 inactivation is because of the formation of the inactive 6-TGDP-Rac1 adduct in CD4 ϩ cells.…”
Section: Inhibitory Effects Of 6-tg and A Redox Agent On Development mentioning
confidence: 57%
“…Each of these GEFs was detected in CLL cells before and after 2 days of culture with CD154-bearing cells (Supplemental Figure 6A), which may induce expression of other GEFs, such as Tiam1 (35). We found that treatment of cultured CLL cells with Wnt5a increased the in vitro exchange activity for RhoA of immune precipitates generated with mAbs specific for either ARHGEF1 or ARHGEF2, but not ARHGEF6.…”
Section: Resultsmentioning
confidence: 72%
“…Furthermore, it is possible that GEFs other than ARHGEF1, ARHGEF2, or ARHGEF6 also contribute to ROR1 signaling. For example, culture of CLL cells with CD154-bearing cells can induce expression of other GEFs, such as Tiam1, which does not appear to be expressed at high levels by nonstimulated CLL cells (35). Conceivably, the particular GEFs recruited by ROR1/ROR2 may be idiosyncratic to the type of cell or its stage of activation/ differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with recent observations showing that in CLL cells, in contrast with normal B cells, Rac1 is not activated by chemokines and does not contribute to CLL cell motility. 32 To explore the effects of the differential Rap1 activity on CLL cell motility, we used siRNAs to knockdown the expression of the 2 Rap1 proteins, Rap1a and Rap1b ( Figure 2B Figure 2G). This indicates that the higher basal Rap1 activity of CD38-expressing MEC1 cells contributes to their increased migration.…”
Section: Cd38 Stimulates Cell Migration Via the Gtpase Rap1mentioning
confidence: 99%